EVALUASI VITAMIN B PADA BISKUIT BAYI SUBSTITUSI CAMPURAN TEPUNG LABU KUNING (Cucurbita moschataDurch) DAN TEPUNG WORTEL (Daucus carrota L) - Cahyani, Afin Regina; Devi, Mazarina; Soekopitojo, Soenar (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
Consumption of foods with adequate nutritional content is very important to achieve optimal growth and development in infants and toddlers. B vitamins are vitamins that function for metabolism in general and the formation of chemicals that function in nerve cells. This causes B vitamins to have an important influence on brain function. This study aimed to analyze the vitamin B content of the product in the form of biscuits substituted with pumpkin flour (Cucurbita moschata Durch) and carrot flour (Daucus carrota L). The content of vitamin B1 (thiamine), vitamin B2 (riboflavin), vitamin B3 (niacin), vitamin B6 (pyridoxine), vitamin B5 (pantothenic) was highest in biscuits substituted with pumpkin and carrot flour by 30%. The more substitution of pumpkin flour and carrot flour, the greater the levels of vitamin B complex in pumpkin and carrot biscuits. This is because pumpkin and carrots are rich in B-complex vitamins